Groups with the Same Prime Graph as the Simple Group $D_n (5)$ - Babai, A.; Khosravi, B. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
Let $G$ be a finite group. The prime graph of $G$ is denoted by $Γ(G)$. Let G be a finite group such that $Γ(G) = Γ(D_n (5))$, where $n ≥ 6$. In the paper, as the main result, we show that if $n$ is odd, then $G$ is recognizable by the prime graph and if $n$ is even, then $G$ is quasirecognizable by the prime graph.